2021
DOI: 10.1021/acs.cgd.1c00709
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Mediated Phase Transformation on Crystal Facets of Carbamazepine–Saccharin Cocrystals

Abstract: The purpose of the present study was to investigate the effect of crystal facets on solution-mediated phase transformation (SMPT) at cocrystal surfaces during dissolution in aqueous media. Previously, we reported that SMPT occurred rapidly at the particle surfaces of various carbamazepine cocrystals in aqueous media (Mol. Pharmaceutics 2020, 17, 10, 3825–3836). However, SMPT has not been studied focusing on the differences between each facet of a single crystal. In this study, a carbamazepine–saccharin cocryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 70 publications
(128 reference statements)
0
2
0
Order By: Relevance
“…We believe that all the results will be valuable for the comprehensive understanding of the thermal stability and engineering applications of ECCs. Since cocrystallization has been applied in many areas, this mechanism will be also valuable for the stability estimation of other organic cocrystals, e.g., the stability of pharmaceutical cocrystals in aqueous solution. …”
Section: Introductionmentioning
confidence: 99%
“…We believe that all the results will be valuable for the comprehensive understanding of the thermal stability and engineering applications of ECCs. Since cocrystallization has been applied in many areas, this mechanism will be also valuable for the stability estimation of other organic cocrystals, e.g., the stability of pharmaceutical cocrystals in aqueous solution. …”
Section: Introductionmentioning
confidence: 99%
“…Surface precipitation is undesirable as it can severely restrict the cocrystal system from reaching the desired supersaturation target . Omori and co-workers studied this phenomenon extensively ,, and showed that (1) the cocrystal may not generate any bulk supersaturation when the surface precipitation is excessive, (2) the surface precipitation rate is a strong function of the coformer type, (3) similar to bulk precipitation, the surface precipitation rate is also affected by the presence of dissolved polymers in the medium, and (4) different facets of a cocrystal may show different surface precipitation rates. These findings stress the importance of systematically selecting coformers, polymers, and surfactants to control the DSP behavior of cocrystal systems to maximize drug absorption through sustained levels of supersaturation.…”
Section: Introductionmentioning
confidence: 99%